Dopaminergic genotype influences spatial bias in healthy adults - Greene, Ciara M.; Robertson, Ian H.; Gill, Michael; Bellgrove, Mark A. (Neuropsychologia, 2010)
Asymmetries of spatial attention are observed in both clinical and non-clinical populations. While lesions of the right hemisphere frequently result in symptoms of left neglect (right bias), the opposite pattern is often observed in healthy subjects, a phenomenon known as pseudoneglect. Pharmacological and animal studies have suggested a critical role for the catecholamines, in particular dopamine and noradrenaline, in modulating the direction and magnitude of spatial attentional bias. In the present study we investigated the effect of two catecholaminergic genes, DBH and DAT1, on performance in the Landmark task, a perceptual measure of spatial bias. 204 healthy participants performed the Landmark task and were genotyped for the DBH C-1021T and DAT1 3′UTR variants. Homozygosity for the DBH T allele, which is associated with relatively increased dopamine and decreased noradrenaline levels, resulted in a significant increase in rightwards spatial bias relative to the C allele. Similarly, homozygosity for the DAT1 9-repeat allele, which is associated with reduced dopamine transporter density, and consequently increased dopamine availability relative to the 10-repeat allele, was found to result in a greater degree of rightward bias. An additive effect of the two markers was also observed, such that the greatest degree of rightward spatial bias was observed in participants who possessed the ‘high dopamine’ alleles of both genes and the lowest degree in those without these alleles. These results provide the first evidence of genetic modulation of spatial bias in healthy adults.